EMPIRICAL MANY-BODY POTENTIAL-ENERGY FUNCTION CALCULATION FOR LITHIUM CLUSTERS IN BCC AND FCC SURFACE SYMMETRIES, AND CHEMISORPTION ENERGY OF ATOMIC OXYGEN ON LITHIUM BCC CLUSTERS - KOLSUZ, N; CIVI, M; ERKOC, S (World Scientific Publ Co Pte Ltd, 1995)
We have investigated the structure and energetics of lithium clusters containing 3 to 10 atoms in different bcc and fee surface symmetries, and the interaction of an oxygen atom with lithium clusters in the bcc(100) and bcc(110) surface symmetries. Calculations have been performed by using an empirical many-body potential energy function, which comprises two- and three-body atomic interactions.
Keywords: Structural Stability; H-Chemisorption; Li Clusters; Microclusters; Energetics; Abinitio; Silicon; Metals